Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan pada PT Satria Bahana Sarana - Pratama, Agung; Widiyanti, Marlina; Yusuf, Muhammad; Ichsan Hadjri, Muhammad (Green Publisher Indonesia, 2024)
This study was conducted with the aim of determining the influence of work motivation and work environment on employee job satisfaction at PT Satria Bahana Sarana. The population in this study is all employees at PT Satria Bahana Sarana in the 2024 period of 893 employees. Based on calculations using the Slovin formula, the sample that became respondents in this study was as many as 110 people or around 14% of the total employees of PT Satria Bahana Sarana using the proportional sampling method. The results of multiple linear regression analysis show that work motivation and work environment have a positive and significant effect on employee satisfaction. Work motivation, it is expected that the company's management in determining employees in each division needs to be evaluated, especially at the level of education and work experience that is in accordance with what the employee has. The work environment, it is hoped that the company can provide more complete facilities and in accordance with the needs of employees.